Selenium-Containing Protein From Selenium-Enriched Spirulina platensis Attenuates Cisplatin-Induced Apoptosis in MC3T3-E1 Mouse Preosteoblast by Inhibiting Mitochondrial Dysfunction and ROS-Mediated Oxidative Damage - Sun, Jing-yi; Hou, Ya-jun; Fu, Xiao-yan; Fu, Xiao-ting; Ma, Jin-kui; Yang, Ming-feng; Sun, Bao-liang; Fan, Cun-dong; Oh, Jinrok (Frontiers in Physiology, 2019)
Selenium-containing protein from selenium-enriched S. platensis (Se-SP) exhibited novel hepatoprotective potential through inhibiting oxidative damage. However, the molecular mechanism remains unclear. Herein, the protective effect of Se-SP against cisplatin-induced oxidative damage and apoptosis in MC3T3-E1 mouse preosteoblast was investigated, and the underlying mechanism was evaluated. The results showed that cisplatin treatment significantly inhibited cell viability of preosteoblast by triggering mitochondria-mediated apoptosis pathway. Cisplatin treatment also caused mitochondrial dysfunction and reactive oxide species (ROS)-mediated oxidative damage. However, Se-SP pre-treatment significantly blocked cisplatin-induced mitochondrial dysfunction by balancing Bcl-2 family expression and regulating the opening of mitochondrial permeability transition pore (MPTP), attenuated cisplatin-induced oxidative damage through inhibiting the overproduction of ROS and superoxide anion, and eventually reversed cisplating-induced apoptosis by inhibiting PARP cleavage and caspases activation. Our findings validated the strategy of using Se-SP as a promising Se species could be a highly effective way in combating oxidative damage-mediated diseases.